MORE PRACTICE AND LIFE ORIENTATION IN VOCATIONAL AND THEORETICAL UNIVERSITY EDUCATION - GRASEDIECK, Dieter (Presa Universitară Clujeană, 2013)
A central component of this study is a survey of German and Romanian companies. Companies from a total of seven different industries (from the energy industry, electronics industry, IT industry, footwear, furniture industry, tax consultancy and engineering) were interviewed. The survey was conducted with the help of a standardized questionnaire with both closed as well as half open questions.